Anti-oxidative and neuroprotective effects of flaxseed on experimental unilateral spinal cord injury in rat - Gholaminejhad, Morteza; Arabzadeh, Somayeh; Akbari, Mohammad; Mohamadi, Yousef; Hassanzadeh, Gholamreza (Journal of Contemporary Medical Sciences, 2017)
Objectives Investigation of anti-oxidative and neuroprotective effects of flaxseed on rats with unilateral SCI. Methods 30 male Wistar rats were randomly assigned to five groups: control (Ctrl), laminectomy, flaxseed, spinal cord injured (SCI) and SCI + flaxseed (treatment) groups. SCI model was induced by placing a 50 g weight for 5 min on to a 2.2 mm Ã— 2.5 mm platform applied to the dura at vertebral level T10. After 4 weeks, the blood of rats in different groups was collected and the influence of flaxseed on antioxidant enzymes and oxidative stress marker level, histologic alterations and locomotion score were assessed. Results Our results showed that in the SCI group, the mean level of Superoxide dismutase (SOD), glutathione peroxidase (GPx) and catalase (CAT) were significantly decreased (P < 0.01), whereas the mean malondialdehyde (MDA) content was significantly increased (P < 0.001) in comparison to the laminectomy group. Furthermore, the mean levels of SOD, GPx and CAT in the treatment group was higher than the SCI group (P < 0.001), while, the mean MDA content in the treatment group was significantly less than the SCI group (P < 0.001). In addition, comparison between SCI and treatment groups determined a significant decrease in tissue degeneration and volume of cavities in the treatment group. However, Basso, Beattie and Bresnahan (BBB) scores were significantly increased in flaxseed-treated rats on days 14 (P < 0.05), 21 and 28 (P < 0.01) after surgery compared with the SCI group. Conclusions Our study for the first time showed the anti-oxidative and neuroprotective effects of flaxseed on experimental unilateral spinal cord injury in rat. Keywords spinal cord injury, flaxseed, oxidative stress, neuroprotective, anti-oxidative